METALLURGICAL WORKSHOP FROM ROZHDESTVENSKOYE SETTLEMENT: ON THE ISSUE OF DEVELOPMENT OF COMMODITY PRODUCTIONIN THE PERM CIS-URALS - Krylasova, N.B.; Podosenova, Yu.A. (Perm Federal Research Centre Journal, 2016)
A large metallurgical workshop with two chimneys and several hearths was studied in 2011-2012 in Rozhdestvenskoye settlement, which is identified with the famous, according to Arab sources, Bulgar town Afkula. It had a universal character, focusing mainly on foundry and forging production, which was complemented by bone-carving, tanning and woodworking productions. The workshop’s scale lets one suppose its craft orientation.